BIOCHEMICAL MARKERS OF BONE RESORPTION, REGULATION OF OSTEOCLASTOGENESIS AND BONE LOSS FOLLOWING LIVER TRANSPLANTATION - Buzulina, V P; Pronchenko, I A; Ermakova, I P; Shmerko, N P; Andrianova, A A; Kornilov, M N; Yaroshenko, E B; Koliashvili, T K (Osteoporoz i osteopatii, 2013)
Methods and results: bone densitometry of L2-L4 and neck of femur, the level in serum of blood some hormones (PTH, vitamin D3, estradiol, testosterone) and cytokines (OPG, IL-6, FNO-a) regulating osteoclastogenesis as well as comparative analyses of two bone resorption markers β-crosslaps and tartrate-resistant acid phosphatase type 5b (TRAP-5b) were fulfilled at different periods following orthotopic liver transplantation. At the early date after operation there were the bone density decrease of L2-L4, the lowering of vitamin D3, estradiol in women, testosterone in men and the elevation of cytokines and of resorption markers. In 1 and 2 years following liver transplantation there were revealed the rise of bone density, the level of PTH, estradiol, testosterone, which were associated with the lowering of IL-6, FNO-a and β-crosslaps while the level of vitamin D3 and TRAP-5b remained stable. Conclusion: at the early date TRAP-5b was more specific marker of bone resorption which did not depend on collagen metabolism in liver. In 1 and 2 years following liver transplantation bone resorbtion was association with level of PTH, FNO-a and OPG.